TYPES AND FORMS OF REFLEXIVE LEARNING TECHNOLOGIES IN THE PEDAGOGICAL EDUCATION SYSTEM - Donayeva Shakhnoza (Scholar Express Journal, 2023)
In modern education, against the background of radical renewal of the goals and tasks of education, the relationship in the form of "teacher-learner" is becoming completely different. Today's teacher's performance of the functions provided for in traditional education is not enough for the quality and effective organization of the lesson process, and the learning activity of the modern learner consists only of his behavior as an "excellent", "active", "disciplined" child. not. In the course of the lesson, the teacher and the learner are raised to the level of subjects of the educational process, in which the learner has the right to analytically accept the quality, quantity, content, presentation tools, methods, methods and forms of the educational materials presented to him and to directly or indirectly convey his conclusions to the teacher
Keywords: pedagogical system; reflexive education; forms